The Political Representation of Women Politicians from Mass-Based Islamic Parties in Palembang City Regarding the Low Representation of Women in Legislative Bodies (A Study on the PAN and PKS Parties in Palembang City) - Kawwami, Afif Musthofa (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
The background of this research provides an in-depth understanding of the representation of female politicians from Islamic mass-based parties in Palembang, highlighting the ongoing issue of insufficient female representation. Despite the implementation of a 30% quota, women's representation in parliament does not reach this threshold due to various obstacles to political participation. This research specifically examines the representation of female politicians in the PAN and PKS parties in Palembang to understand both the presence of female politicians in the city and the central-level policies supporting women in the region. In Palembang, the PAN party allocates a 38% quota for female politicians, while the PKS party allocates a 30% quota. This study employs descriptive qualitative methods and was conducted in Palembang. Data were collected through in-depth interviews using purposive sampling techniques. Primary data sources include interviews, while secondary data sources include literature reviews. The findings reveal that in the PAN party, women have a 38% quota, supported by an organization called National Mandate Women (PUAN) that handles recruitment. In the PKS party, the women's quota is 30%, with recruitment conducted through various channels, including assessments of cadres' abilities and expertise. The 2019 elections showed a shift, with women becoming more independent in their political decisions, previously influenced by men's political preferences.